Public Distrust of Makassar City Government In Handling The COVID-19 Outbreak - Delly Mustafa; Muhammad Ahsan Samad; Indriati Amirullah (Journal of Governance, 2022)
This study aims to analyze how much public distrust of the Makassar City government is in dealing with the Covid-19 outbreak. This study not only examines how the information exposure process occurs but also analyzes the perceptions and impacts caused by the exposure process. We collected information through field interviews with 10 informants, literature studies such as journals, books, official websites, and reliable news portals. Data collected through observation includes information on the number of people infected, recovered, and died, as well as government operations related to Covid-19 (lockdown, rapid tests, and reporting of humanitarian aid affected by Covid-19). The results showed that at first, the pandemic made the community obedient and obedient to government policies, but various incidents such as forced pick-up of bodies suspected of being infected with the COVID-19 virus but health workers were unable to show the final results of the tests, the lack of availability of health-protective equipment for paramedics also created seeds of distrust. society on government policies, so that people hold resistance in the form of disobedience to government policies. In this study, two approaches are recommended for the government to be able to restore public trust, the two components are openness and competence. This component can be used as a consideration for the government to restore public trust which is already disappointed with various confusing policies that seem to be not in favour of the community.